THE IMPORTANCE OF THE ENGLISH LANGUAGE AS A FOREIGN LANGUAGE IN THE EDUCATIONAL INSTITUTIONS OF UZBEKISTAN AND TEACHING PROCESS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
In this article , the status of the  English language in the world is enhancing and the teaching of the English in all educational organization and institutions in Uzbekistan , especially at schools, is about  the decisions of our government about acquiring a second language and what kinds of methods are beneficial for students understanding in the classrooms.